Argamassa com substituição parcial do cimento por resíduos industriais - Moura, Alexandre Amado de (2018)
Degradation of the environment and its consequences result in stricter regulations imposed by the public authorities in certain productive sectors. The cement industry is responsible for the emission of approximately 7 wt. % of the CO2 released into the atmosphere from anthropogenic sources. In order to find possible substitutes for mortar and concrete cement and to contribute to the reduction of CO2 emissions, the performance of sugarcane bagasse ash (SCBA) and waste glass powder (WGP) were evaluated. SCBA is produced in the sugar and alcohol industries after the burning of sugarcane bagasse to generate electricity. The WGP is an underutilized industrial waste, systematically discarded by the cutting industries. Their chemical compositions are favorable due to the high content of silicon and calcium. Both residues have been discarded in landfills or open dumpsters, an unsuitable and unsustainable practice. A more modern way of dealing with these materials and contributing to sustainable development is their incorporation into the productive chain of other products. The chemical and physical characteristics of SCBA and WGP were monitored from standardized tests and analytical techniques such as X-ray diffraction, X-ray fluorescence, thermogravimetric analysis, scanning electron microscopy and nitrogen adsorption-desorption. The results indicated that the main physico-chemical and mechanical properties of the mortars were maintained due to the pozzolanic effect of these additions. The best results were obtained with 20 wt. % of WGP and a blend of 5 wt. % of WGP and 5 wt. % of SCBA. Its resistance to simple compression was equivalent to the reference mixture. The characterization techniques indicated that there should be a synergistic effect between SCBA and the WGP in terms of kinetic aspects and compressive strength. The results indicated that the use of these industrial residues is a consistent way of partially replacing the cement in the composition of mortars and concretes